Policy Imlementation of Conflict Mitigation (Study on Implementation of Regional Regulation No 2/2013 on Disaster Mitigation in Poso Regency of Central Sulawesi Province) - Risaldy Kalembiro; Bambang Santoso Haryono; Romy Hermawan (Sekolah Pascasarjana Universitas Brawijaya, 2018)
This research aims to analyze the Policy Implementation of Conflict Mitigation in Poso Regency which adopted the Regulation of Central Sulawesi Province Governor No 2/2013 on the Implementation of Disaster This research used descriptive research type with qualitative approach. To analyze, the writer used Implementation Model of Van Metter and Van Horn (1975). The research finding was in order that Poso City became a safe, peaceful and tranquil city with Sintuwu Maroso as a slogan. Besides, the government also formed Sub District Integrated Team in order to mitigate the conflict such as the formation of Interreligious Harmony Forum (FKUB), National Reform Forum (FPK) and Society Early Alertness Forum (FKDM). However, the formation of sub district forum was not maximal yet because there were forums in sub districts which were not formed yet. The next problem was the recovery fund which was not on target yet. The government was not open yet either in giving any deep information related to the conflict mitigation. Nevertheless, the entire elements related to the conflict mitigation continued to make any effort as maximal as possible to reduce the available conflict intensity in Poso Regency. The conclusion of the research was that the policy implementation of conflict mitigation had not run maximally yet and the Regional Government did not own the permanent Regional Regulation related to the conflict mitigation.